Spectral Studies of Ln(III) Complexes with Pyridine Propanamine-γ-(4-chlorophenyl)-N,N-dimethyl-2-maleate - V. LOKHANDE*, MANOHAR; T. TAJANE†, SHARAD; GEORGE A‡, K. (Asian Journal of Chemistry, 2024)
Complexes of La3+, Pr3+, Nd3+, Sm3+, Gd3+, Tb3+ and Dy3+ with pyridine propanamine-γ-(4-chlorophenyl)-N,N-dimethyl-2-maleate have been prepared, structures of the complexes have been established on the basis of elemental analysis, magnetic moment, infrared, thermal analysis, X-ray powder diffraction and electronic spectra. The ligand is bonded through nitrogen of propanamine and nitrogen of pyridine with metal ions. The magnetic moment studies indicate that, it is slightly participation with 4ƒ electrons in bonding. The X-ray powder diffraction studies indicate that, the unit cell is monoclinic and space group of complexes is C2/m or Pc/m. This ligand is anti-histaminic and active towards gram positive and gram negative bacteria.